Teacher Strategies in Greeting-Based Character Education: Fostering Students’ Friendly Traits at State Islamic Elementary School 1 Merangin - Fikri, M. Zhaharil; Pristian Hadi Putra; Novri Pahrizal; Indah Herningrum (Institut Agama Islam Negeri Kerinci, Indonesia, 2024)
This study explores the strategies employed by teachers at State Islamic Elementary School 1 Merangin in cultivating greeting practices as a means of fostering students’ friendly character. Using a qualitative approach, data were collected through participatory observation, in-depth interviews with the school principal, teachers, and students, as well as document analysis of instructional activities and school-based cultural programs. The findings reveal three major points. First, greeting practices are regarded as crucial in shaping students’ friendly character. They contribute to the development of positive social relations, strengthen etiquette, reduce conflicts, and nurture a welcoming personality. Second, teachers adopt various strategies to instill greeting habits, including socialization and internalization of greeting culture, introducing the meaning and benefits of greetings, serving as role models, and implementing evaluation and reward systems. Third, the outcomes of these strategies are evident in the consistent practice of greetings among students, the establishment of a friendly classroom atmosphere, improved relationships between students and teachers, and a noticeable reduction of potential conflicts. This study underscores the pivotal role of teachers as agents of character education in Islamic elementary schools. It highlights how simple yet consistent practices such as greetings can effectively integrate social values, etiquette, and Islamic morality into daily school life. The findings have broader implications for Islamic education, suggesting that greeting-based character education can nurture a generation of students characterized by friendliness, respect, and strong moral integrity.